When miners become “foreigners”: Competing categorizations within gold mining spaces in Guinea - Bolay, Matthieu (My University, 2014)
Drawing on ethnographic research and problem-centered interviews in Guinean mining areas, this paper presents a comparative reading of the conflicting conceptions of what constitutes a “mining community.” First, I explore how independent artisanal miners describe and identify their activity. The weight of autochthony conventions is discussed concerning their insertion both in the mining fields and in their living locations. Second, I focus the case study on how the corporate social responsibility (CSR) interventions toward the mining community, commissioned by a gold mining company in Guinea, are interpreted by the artisanal miners. The analysis of the deployed discourses and related interventions delineate what is defined as the mining community in CSR programs, and how these interventions shape new understandings of the company׳s territory among the miners.
Using a boundary work approach, the paper shows how CSR interventions symbolically transpose the spatial concession border into symbolic and social boundaries among the artisanal mineworkers. CSR discourses and interventions transform “trespassers” into “foreigners”, as opposed to “natives”, who are often viewed as “traditional sedentary workers” by the mining company. In doing this, CSR programs reinforce and standardize autochthony-based relations, and extend autochthony boundaries in all segments of the gold mining socio-technical system. The attachment of these initially separated categories creates an idealized figure of “traditional” artisanal mining, while also stigmatizing the itinerant artisanal miners. As a consequence, I will discuss the emergence of conflict situations regarding access to mining spaces and resources within the surrounding villages.
Keywords: Guinea; Artisanal and small scale mining (ASM); Corporate social responsibility; Mobility; Autochthony